Fiscal policy, intercountry adjustment and the real exchange rate within Europe - Allsopp, Christopher; Vines, David; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructures and Logistics in Brussels, 2008)
In EMU, a country may have difficulty ensuring stability in the face of asymmetric shocks; the response may be unstable, or, even if not, the real exchange rate might overshoot. Fiscal policy may help to stabilise inflation and also to target the real exchange rate. The paper argues that an improved fiscal policy process might result in improved macroeconomic performance within Europe. Within EMU, a country may have difficulty ensuring stability in the face of asymmetric shocks; the response may be unstable, or, even if not, the real exchange rate might overshoot. In this context, the rules of the SGP may interfere with the control of inflation control, with the short-run stabilisation of demand, and also with the longer term adjustment of intra-European real exchange rates. We recommend using fiscal policy to stabilise inflation and also to target the real exchange rate rather than deficits or debt. Such a policy would require a more active use of fiscal policy.
Economic Papers.